Evaluating The Application of Library Information System Technology using the PIECES Method in Remote Areas - Yudhana, Anton; Herman, Herman; Suwanti, Suwanti; Biddinika, Muhammad Kunta (ILKOM Jurnal Ilmiah, 2023)
Over five years, the implementation of the library information system at IKIP Muhammadiyah Maumere faced a challenge, frequent errors during data input that hindered users from fully utilizing the system. These issues not only affected users’ interest but also highlighted the significance of the human factor in shaping the quality of an information system. To make full use of the system, it was crucial to identify and address the problems associated with it. This research delved into the experiences of 242 library information system users, including lecturers, students, and librarians, by using the PIECES method. The goal was to analyze users’ satisfaction and uncover any underlying issues within the system. The results of the PIECES analysis revealed average satisfaction scores, showcasing users' contentment with the system's performance (3.77), information (3.79), economy (3.80), control (3.77), efficiency (3.77), and service (3.89). These findings suggest that the library information system has been meeting users' expectations. However, a significant problem emerged in the performance variable, particularly in the system stability. Additionally, issues related to data compatibility, duplication in storage, and users’ authority management, access control, and system errors were observed in the information and control variables. Based on these identified challenges, recommendations for system improvement were made by targeting low satisfaction levels. Proposed solutions involve enhancing data management, storage practices, user access control, and reducing the risk of system errors, ensuring more efficient and reliable library information system.